2002
DOI: 10.1677/joe.0.1720031
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acids promote the action of aromatase and 17beta-hydroxysteroid dehydrogenase type 1 on the biosynthesis of 17beta-estradiol in placental cells

Y Li2,
et al.

Abstract: The biosynthesis of 17 -estradiol (E 2 ) in human placenta involves the actions of aromatase and 17 -hydroxysteroid dehydrogenase type 1 (17HSD1). Aromatase, an enzyme complex comprised of P450aromatase (P450arom) and NADH-cytochrome P450 reductase, converts androgens to estrogens, whereas 17HSD1 catalyzes the reduction of estrone to E 2 .In the present study, the effects of retinoic acids (RAs) on P450arom and 17HSD1 expression in placental cells were investigated. Treatment with all-trans-RA (at-RA) or 9cis-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Our recent study clearly showed that P450arom and 17HSD1 are expressed in cultured CT cells isolated from normal human placenta of the first trimester [18]. In the cell culture system of the above investigation, VCT cells counted for the major portion of the cell population, because only the tips of chorionic villi were collected for the purification of CT cells.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our recent study clearly showed that P450arom and 17HSD1 are expressed in cultured CT cells isolated from normal human placenta of the first trimester [18]. In the cell culture system of the above investigation, VCT cells counted for the major portion of the cell population, because only the tips of chorionic villi were collected for the purification of CT cells.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, 17HSD1 was immunolocalized in invasive CT cells of full-term placenta [17]. Our recent study demonstrated that cultured CT cells purified from first-trimester placenta express both P450arom and 17HSD1 and are capable of converting dehydroepiandrosterone and A-dione to E 2 [18]. However, it is not clear whether these two steroidogenic enzymes are present in various CT cells of early placenta in vivo.…”
Section: Introductionmentioning
confidence: 96%
“…HSD17B1 is expressed in the syncytiotrophoblast cells of the placenta [22][23][24] and ovarian granulosa cells [23,25,26], and both of these cell types are involved in de novo estrogen biosynthesis. Similarly to P450 aromatase (CYP19A1), the expression of HSD17B1 is related to follicular differentiation and positively correlates with the follicular E2 concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Increased biosynthesis of estrogens [estrone (E 1 ) and estradiol (E 2 )] and their oxidative metabolism to catechols and quinones in the breast have been associated with the induction of breast cancer [1][2][3][4]. Breast cells are continuously exposed to significant levels of estrogens, estimated at 50-400 pmol/g of breast tissue [5][6][7][8][9][10] and ∼2 mol/L in nipple fluid [11,12].…”
Section: Introductionmentioning
confidence: 99%